Internet fraud casebook : the World Wide Web of deceit - Wells, Joseph T. (John Wiley & Sons, 2010)
"This one-of-a-kind collection consists of actual cases written by fraud examiners out in the field. These cases were hand selected from hundreds of submissions and together form a comprehensive picture of the many types of Internet fraud how they are investigated, across industries and throughout the world. Topics included are phishing, on-line auction fraud, security breaches, counterfeiting, and others. The cases each are entertaining stories in their own right, as well as educational, and readers will enjoy reading them as they grow to understand more about the developing world of Internet fraud"